A comparative evaluation of stress distribution between an All-on-Four implant-supported prosthesis and the Trefoil implant-supported prosthesis: A three-dimensional finite element analysis study - Jaisudhaa Murugaian; Lambodaran Ganesan; M S Sathya Shankar; H Annapoorni (Wolters Kluwer Medknow Publications, 2022)
Aim: The primary aim of this study is to analyse the stress distribution between an ALL ON FOUR implant supported prosthesis and the TREFOIL implant supported prosthesis with 3D finite element models. Settings and Design: An in vitro perspective Materials and Methods: Two mandibular three-dimensional Finite Element Models were constructed by the CREO version 5 software, in which Model A depicts a mandible with ALL ON FOUR implant supported prost hesis and Model B will depict TREFOIL implant supported prosthesis. Model A contains four implants, two anterior straight and posterior tilted implants (30°), a bar and denture containing acrylic teeth. In Model B, it contains three straight implants and a prefabricated compensatory bar with standardised dimensions. To evaluate and compare the stress distribution between the bone and implant interface, one deleterious cantilever load of upto 300 N is applied on the second molar bilaterally and simultaneously. Another full bite biting load of 150 N is given bilaterally and simultaneously on the central groove of premolars and molars. Statistical Analysis Used: The results of the simulations obtained were analysed in terms of Von Mises equivalent stress levels at the bone -implant interface. Results: The results of loading 1 showed that the maximum Von Mises stress was recorded in the anterior implant region of the Trefoil system (Model B) when compared to All on four concept. The results of loading 2 showed that the maximum Von Mises stress were recorded in the anterior implant region Trefoil system (Model B) when compared to All on four concept. Conclusion: This invitro study concludes that All on Four implant supported prosthesis showed better stress distribution when compared to the Trefoil concept.